Linear response in the AC susceptibility of vortices in YBa2Cu3O7 crystals with columnar defects - Nieva, Gladys; Pasquini, G.; Levy, P.; Civale, L.; Nieva, G.; Lanza, H. (Elsevier, 1997)
Fil: Pasquini, G. Comisión Nacional de Energía Atómica. Departamento de Física; Argentina